Study On The Accuracy Of Tree’s Diameter Measurement By Laser Range Finder System - Mohd Rusdy, Yaacob; Miskon, Muhammad Fahmi; Chan, Xin Zhi (2014)
This paper presents a study on the accuracy of laser range finder system for the measurement of tree’s diameter. The study has been conducted by using Hokuyo URG-04LX-UG01 Laser Range Finder. The measurement was done in different distances from the measured tree at a fix elevation in two different modes; sensor held in hand and sensor mounted on a tripod. An algorithm was developed to derive the formula for calculating the diameter by applying the principle of circle tangent theory. The results obtained are the values of accuracy for the diameter measurement of a tree for different distances between the sensor and the tree measured which are presented in graphs. Finally the accuracy levels between the two modes are compared to find the most preferable mode for the measurement in real application.